Kardiochirurgia wad wrodzonychTransfusion-free anatomical correction of transposition of the great arteries (dTGA) in a 4.4-kg neonate - Buczyński, Michał; Zachurzok-Buczyńska, Agnieszka; Wites, Marek; Stanek, Piotr; Pająk, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Because of the great risk of peri- and postoperative bleeding and priming volume, complex cardiac surgery employing cardiopulmonary bypass (CPB) and deep hypothermy in neonates usually requires transfusion of the blood products. However, for the sake of the side effects of blood transfusion and religious beliefs, efforts of transfusion-free complex cardiac surgery are made. We report the case of a 4.4-kg Jehovah’s witness neonate, who underwent anatomical correction of the transposition of the great arteries (dTGA), without the use of autologous blood component transfusion.